The use of remote sensing and GIS in the identification and vulnerability detection of coastal erosion as a hazard in False Bay, South Africa - Callaghan, Kerry Lee (Stellenbosch : Stellenbosch University, 2014)
Thesis (MSc)--Stellenbosch University, 2014.